History and Patterns of Islamic Law Taqnin in Indonesia - Fauziati, Fauziati; Abbas, Syahrizal (Abdurrauf Journal of Islamic Studies, 2024)
The applicable law in Indonesia consists of three major legal systems, namely Islamic law, customary law and ex-Dutch colonial law. Islamic law as a legal system that still exists and is in force in Indonesia certainly has its own dynamics from the historical perspective of its implementation. Moreover, it is located between two large legal systems, namely customary law and ex-colonial law. This study attempts to analyze the history of Islamic law and the existence of Islamic law in Indonesia. The research method used is a normative legal research method with a historical approach. The use of a historical approach is because the main focus of the study is analyzing the history of Islamic law and the existence of Islamic law in Indonesia. The data used are primary legal materials and secondary legal materials. Primary legal materials are the Marriage Law, KHI, Sharia Banking Law, Religious Courts Law. The secondary legal materials used are books, journals and relevant research results. The research results show that historically Islamic law has been left behind and marginalized as a result of VOC policies which tended to elevate customary law and colonial law and emphasized Islamic law. The existence of Islamic law developed again after independence, marked by the many regulations governing Islamic law, Islamic law was even used as raw material in formulating national law in Indonesia. What's more interesting is that the majority of the raw materials used come from books written by Imam Syafi'i, such as during the formulation of the KHI. Hukum yang berlaku yang berlaku di Indonesia terdiri dari tiga sistem hukum besar, yaitu hukum Islam, hukum adat dan hukum eks kolonial Belanda. Hukum Islam sebagai salah satu sistem hukum yang masih eksis dan berlaku Indonesia tentu memiliki dinamika tersendiri dalam perspektif historis permbelakuannya. Apalagi berada di antara dua sistem hukum yang besar yakni hukum adat dan hukum eks kolonial. Kajian ini berusaha menganalisis sejarah taqnin hukum Islam dan eksistensi hukum Islam di Indonesia. Metode penelitian yang digunakan yaitu metode penelitian hukum normatif dengan pendekatan historis. Penggunaan pendekatan historis karena fokus utama kajian menganalisis sejarah taqnin hukum Islam dan eksistensi hukum Islam di Indonesia. Data yang digunakan yaitu bahan hukum primer dan bahan hukum sekunder. Bahan hukum primer yaitu UU Perkawinan, KHI, UU Perbankan Syariah, UU Peradilan Agama. Bahan hukum sekunder yang digunakan yaitu buku, jurnal dan hasil penelitian yang relevan. Hasil penelitian menunjukkan bahwa secara historis hukum Islam memang mengalami ketertinggalan dan terpinggirkan akibat dari kebijakan VOC yang cenderung mengangkat hukum adat dan hukum kolonial serta menekankan hukum Islam. Eksistensi hukum Islam kembali berkembang pasca kemerdekaan yang ditandai dengan banyaknya regulasi yang mengatur tentang hukum Islam, bahkan hukum Islam dijadikan sebagai bahan baku dalam memformulasikan hukum Nasional di Indonesia. Hal menariknya lagi, mayoritas bahan baku yang digunakan berasal dari kitab karangan Imam Syafi’i seperti pada saat perumusan KHI.